Kinetics and inhibition by some amino acids of arginase in cattle rumen tissue - Erisir, M; Ozan, ST (Scientific Technical Research Council Turkey, 2000)
The effects of some amino acids on arginase activity in cattle rumen tissue were studied. L-amino acids, such as valine, leucine, isoleucine. ornithine, cysteine, proline, lysine inhibited the enzyme activity noncompetitively. On the other hand, histidine and hydroxyproline were not determined to have any inhibitory effect on the enzyme activity. Isoleucine, valine, leucine, cysteine, ornithine were more strongly inhibitory than proline and lysine.
Keywords: arginase; cattle rumen tissue; amino acids